Flow Assessment of Self-Compacted Concrete incorporating Fly Ash - Memon, M. A.; Memon, N. A.; Memon, A. H.; Bhanbhro, R.; Lashari, M. H. (Engineering, Technology & Applied Science Research, 2020)
Flowability is one of the prime characteristics of good concrete and plays a key role in Self Compacting Concrete (SCC). This study assesses the flowability of SCC with reduced cement content which is replaced by fly ash. Several mixes were prepared by using 5% to 30% fly ash. From the experimental work it was realized that by adjusting a suitable percentage of Super Plasticizer (SP), fly ash dosage can be increased with satisfactory fresh properties of concrete in accordance with the guidelines of EFNARC. At T50cm time the optimum amount of SP was 2%. It was noted that with increase in dosage of fly ash the slump flow increased but T50cm and V-funnel time were reduced. J-Ring height value varied from 9 to 10 for all mixes.